Vertical Distribution of Particulate Matter in the Clarion Clipperton Zone (German Sector)—Potential Impacts From Deep-Sea Mining Discharge in the Water Column - Gillard, Benjamin; Harbour, Rob P.; Nowald, Nicolas; Thomsen, Laurenz; Iversen, Morten H. (Frontiers in Marine Science, 2022)
Most studies on the potential impacts of deep-sea mining in the Clarion Clipperton Zone (CCZ) have largely focused on benthic ecosystems but ignore the pelagic environment. To model full-scale impacts, it is important to understand how sediment discharge might affect the pelagic zone as well. This study combines in situ optics, hydrography, and remote sensing to describe particle abundance and size distribution through the entire water column in the CCZ (German sector). CCZ surface waters were characterised as productive over the year. During the winter, we observed the formation of a sharp transition zone in Chla concentration, identifying the area as a productive transitional zone toward a more depleted ocean gyre. In the German sector, median particle size was small (±77 μm), and large particles (> 300 μm) were rare. By assessing particle flux attenuation, we could show that the presence of a thick OMZ plays an essential role in export and transformation of settling aggregates, with strong diel variations. We suggest that the combination of small aggregate size, bottom currents and slow seafloor consolidation may explain the extremely low sedimentation rate in the CCZ. We conclude that sediment incorporations and ballasting effect on settling particulate matter represent the most significant hazard on midwater and benthic ecosystems.